The investigation of studies on case study method in education - ŞENGÜL, SARE (My University, 2021)
The case study method is a method that helps fill the gap between theory and practice in the teaching environment by bringing students face to face with real life experiences [1]. The case study method has application in different disciplines and students can learn problem solving, critical thinking, reflective thinking, decision making, multicultural awareness, etc. It is very effective in gaining skills [2]. The study aimed to examine the researches on the case study method in education through systematic review. Thus, a general framework from the descriptive features of the relevant researches from their aims to their results was drawn and their tendencies were evaluated. In the study, a total of 48 researches that consisted of 21 articles, 20 master’s thesis and 7 doctoral dissertations published between 2010-2020 were included. The researches were examined within the scope of the education field that the case study method was used, purpose, method, sample, data collection tools and results by content analysis. The obtained data were presented on tables with frequencies. As a result of the study there were determined that as the education area where the case study method was used, that the most researches were made in the fields of teacher education, chemistry education and Turkish education; that quantitative research methods were mostly preferred; that mostly working with students and preservice teachers; that it was determined that scale and achievement tests were used. When the researches examined were evaluated within the scope of their purposes, the effects of the use of the case study method on academic achievement were related to critical thinking, creative thinking, social problem solving, decision making, etc. in the field of education. It was observed that the effect on gaining skills was tried to be determined. Within the scope of the results obtained, the findings regarding the effects of the use of the case study method on knowledge, skills and affective areas were determined. In this direction, different studies can be designed and implemented with the participation of interdisciplinary studies on the use of the case study method in the field of education and with the participation of student groups at all levels, starting from younger age groups, instructors, teachers and preservice teachers who are the implementers of the method and students’ parents who have an important role in the education of students. The effect size can be increased by sharing the results.
Keywords: Education; case study method; systematic review